Emotions Have Many Faces: Inuit Lessons - Briggs, Jean L. (Anthropologica, 2022)
This paper was originally delivered at Memorial University in a distinguished lecture series. The author describes how her lifelong study of Inuit emotional life grew out of her attempt to understand the experience of being ostracized, as a novice anthropologist in an Inuit camp, for inappropriate expression of emotion. After outlining several emotion concepts that are composed differently in Inuktitut and in English, and describing the role played by these concepts in the social relationships of Inuit, the paper describes some important socialization experiences that Inuit children have, which help them to become actors in the emotional plots of Inuit life. In playful mode, adults ask children questions that the child being questioned perceives as personally threatening, and then dramatize the consequences of various answers. In this way, adults create, or raise to consciousness, issues that will be of great consequence for the child’s life; and emotions acquire meaning and power through experiential webs of association. Analyzing these phenomena led the author to a growing appreciation of the essential role of emotional dilemmas in Inuit social life; and on the broader plane, it led to a deeper understanding of the constructive power of emotions in social life generally